Bimetallic organic framework derivation of three-dimensional and heterogeneous metal selenides/carbon composites as advanced anodes for lithium-ion batteries. Issue 23 (8th June 2020) - Wang, Ke; Wang, Yaping; Zhang, Yifang; Liu, Fei; Shi, Junrong; Liu, Shengyuan; Xie, Xuefang; Cao, Guozhong; Pan, Anqiang
Abstract : Heterogeneous structures have been attracting increasing attention in energy storage and conversion applications due to the phase interface and synergistic effect of multiple components. Abstract : Heterogeneous structures have been attracting increasing attention in energy storage and conversion applications due to the phase interface and synergistic effect of multiple components. Herein, bimetal organic framework analogues were introduced to construct a Zn/Co bimetallic selenide heterostructure within a 3D-porous N-doped carbon matrix by a NaCl template-assisted lyophilization and annealing process. The cross-linked 3D network can enhance the transport kinetics for both lithium ions and electrons. The stress resulting from the cycling process can be released by interconnected channels in the composite. ZnSe and CoSe2 experience electrochemical reactions at different potentials, which can buffer volume changes mutually to effectively increase structural stability. Meanwhile, abundant active sites due to the heterostructure enhance pseudocapacitive performance and reaction kinetics, resulting in high specific capacity and good rate performance. As anode materials for lithium-ion batteries, the three-dimensional ZnSe/CoSe2 -C composite exhibits a high reversible capacity of 700 mA h g −1 after 500 cycles at 1 A g −1 .